DGMATH: Media Digital Matematika Berbasis Android untuk Siswa Sekolah Dasar Materi Operasi Bilangan Menggunakan Metode RnD - Yuniarti, Dwi Ariani; Intyanto, Gramandha Wega; Pawening, Ari Setyani (Edumatica : Jurnal Pendidikan Matematika, 2022)
Learning mathematics during the COVID-19 pandemic encountered many obstacles, especially at the elementary school level. The application of learning at home makes elementary school students less guided so that the delivery of material is not optimal. Rapid technological developments can facilitate the implementation of mathematics learning for elementary school students, namely the use of interactive digital media in learning mathematics. This study aims to design an application that can be used as a medium for learning mathematics, especially the material for number operations, this application is named DGMATH. The method used is the Research and Development (RnD) method with a 4D model (Define, Design, Development and Disseminate). The instrument used is a usability test, namely the usability heuristic model and the System Usability Scale. The usability heuristic model with five (5) usability indicators, namely learnability, memorability, efficiency, errors and satisfaction were addressed to four (4) experts. The results obtained are that four indicators are included in very good criteria, namely 4.5 for the learnability and satisfaction indicators, 4.125 for the memorability and efficiency indicators, while 3.5 for the errors indicator which is included in the good criteria. The System Usability Scale model is addressed to 30 students who are end users of the DGMATH application with a score of 77.3 which is included in the acceptable criteria.